2013
DOI: 10.1111/jopr.12032
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Marginal Fidelity and Surface Roughness of Porcelain Veneers Fabricated by Refractory Die and Pressing Techniques

Abstract: The mean surface roughness of veneers in cervical, mesio-incisal, and disto-incisal areas was 0.41 ± 0.25, 0.33 ± 0.14, and 0.32 ± 0.14 μm, respectively, for group I; and 0.31 ± 0.11, 0.36 ± 0.18, and 0.29 ± 0.11 μm, respectively, for group II. Intra- and intergroup comparisons showed no statistically significant values for all areas (p > 0.05). In 144 margins evaluated for each group, a visible gap was present in 15 (10.4%) and 18 (12.5%) recordings at 7 days for groups I and II, respectively. They increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Another method is the pressing ceramic technique involving waxing up the restoration to the proper form and pressing it under pressure into the evacuated mold, similar to the lost wax technique for metal. The most advanced technique uses the Computer-aided Designing/Computer-aided Manufacturing "CAD/ CAM" system [2].…”
Section: Introductionmentioning
confidence: 99%
“…Another method is the pressing ceramic technique involving waxing up the restoration to the proper form and pressing it under pressure into the evacuated mold, similar to the lost wax technique for metal. The most advanced technique uses the Computer-aided Designing/Computer-aided Manufacturing "CAD/ CAM" system [2].…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al found the conventional feldspathic method to have better results [6]. Jha et al concluded that both techniques showed similar results [8]. Ghaffari et al…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al found the conventional feldspathic method to have better results [ 6 ]. Jha et al concluded that both techniques showed similar results [ 8 ]. Ghaffari et al showed that CAD-CAM produced better results when compared to the conventional method [ 9 ].…”
Section: Reviewmentioning
confidence: 99%
“…Marginal adaptation of all the laminate veneers in each group was evaluated qualitatively on epoxy resin dies (obtained from post-restorative impressions) at baseline and at each follow-up under scanning electron microscope (SEM). [ 23 ] All epoxy resin dies were gold sputtered [ Figure 2 ] to form a uniform layer of thickness of about 30–40 nm over the specimens to make them conductive of electricity and help in scanning by high energy electron beam. All the four margins of the laminates (Cervical, Incisal, Mesial, and Distal) were evaluated at the midpoint of the respective margin under × 200 magnification.…”
Section: Methodsmentioning
confidence: 99%